Acute effects of calcium supplements on blood pressure: randomised, crossover trial in postmenopausal women. Issue 1 (January 2017) - Billington, E.; Bristow, S.; Gamble, G.; de Kwant, J.; Stewart, A.; Mihov, B.; Horne, A.; Reid, I.
Abstract Summary Calcium supplements appear to increase cardiovascular risk, but the mechanism is unknown. We investigated the acute effects of calcium supplements on blood pressure in postmenopausal women. The reduction in systolic blood pressure was smaller after calcium compared with the placebo in the hours following dosing. Introduction Calcium supplements appear to be associated with increased cardiovascular risk; however, the mechanism of this is uncertain. We previously reported that blood pressure declined over a day in older women, and that this reduction was smaller following a calcium supplement. To confirm this finding, we investigated the acute effects of calcium supplements on blood pressure. Methods This was a randomised controlled crossover trial in 40 healthy postmenopausal women (mean age 71 years and BMI 27.2 kg/m2 ). Women attended on two occasions, with visits separated by ≥7 days. At each visit, they received either 1 g of calcium as citrate, or placebo. Blood pressure and serum calcium concentrations were measured immediately before, and 2, 4 and 6 h after each intervention. Results Ionised and total calcium concentrations increased after calcium (p < 0.0001 versus placebo). Systolic blood pressure decreased after both calcium and placebo, but significantly less so after calcium (p = 0.02). The reduction in systolic blood pressure from baseline was smaller after calcium compared with placebo by 6 mmHg at 4 h (p = 0.036) and by 9 mmHg at 6 h (p = 0.002). The reduction in diastolic blood pressure was similar after calcium and placebo. Conclusions These findings are consistent with those of our previous trial and indicate that the use of calcium supplements in postmenopausal women attenuates the post-breakfast reduction in systolic blood pressure by around 6–9 mmHg. Whether these changes in blood pressure influence cardiovascular risk requires further study.